Automation Identify and Counter Threats to Information on the Internet - Грищук, Р. В.; Лагодний, О. В.; Носова, Г.Д.; Лукова-Чуйко, Н. В. (Science-based technologies, 2018)
Pre-conditions of necessity of exposure of informative threats are in-process considered in the certain segment of network the Internet the objects of influence, the analysis of features of organization of information is conducted in a network, grounded necessity of active introduction of automation of these processes for modern terms. For today network the Internet became the ideal mean of delivery of informative threats in the format of phototypograph audio- or video of reports to any object of influence or having a special purpose audience. the use of information in the certain forms of presentation allows to carry out psychological influence on objects with the purpose of forming of the desired effects with the high degree to reserve of such influences. The analysis of model of exchange information is conducted between the users of network the Internet on the example of social networks for subsequent researches. Grounded impressionability of this process is to introduction of negative influences on the objects of influence. Introduction of the automated process of analysis of the opened information generators is offered with the purpose of exposure of destructive psychological influence on certain objects. There are selected the key problems of decision of question of monitoring of the Internet with the purpose of exposure of negative informative influences On the basis of the conducted researches offered approach to the exposure of signs of informative threats the objects of influence. Certainly the basic requirements are to the developed method of their exposure as a result of monitoring. The step-by-step method of exposure of informative threats is developed. The compressed description of actions at every step of implementation of process of exposure of negative influences is in-process given on certain objects. Offered approach with complex application of the developed software and step-by-step treatment of the selected volume of information.